Settlement of Land Acquisition Conflicts in the Contraction of International Airport in Yogyakarta Special Region - Zuliyah, Siti; Absori, Absori (International Journal of Psychosocial Rehabilitation, 2019)
The inhibition of the construction of the International Airport in the Special Region of Yogyakarta is caused by the rejection of the affected community because some of the land which becomes the construction site belongs to the community and another part belongs to the PAG (Paku Alam Ground), because of the status of this land status, it has caused the community to reject in addition to the compensation factor that are not clear, lack of certainty of relocation and employment problems. If the conflict does not receive serious attention and does not look for a solution that can be accepted by all parties to the dispute, it is feared that it will accumulate in the form of violence. This study intends to formulate describing the resolution of conflicts in land acquisition for the construction of the International Airport in the Special Region of Yogyakarta. This research is an empirical study, using a sociological juridical approach. The data analysis uses descriptive qualitative method. Conflict resolution in land acquisition in the construction of the International Airport in the special area of Yogyakarta is done through consultation and mediation, but both ways can be said to fail because there is no meeting point between the government and the community in resolving conflicts. In addition to the deliberation and mediation method, a consignment method is also carried out, namely safekeeping of compensation provided to the entitled parties who refuse. The consignment was carried out in the Wates District Court, but the method of consignment was also unsuccessful because the community members felt compelled to accept compensation determined by the government, this proved that there were still around are families who has not yet taken compensation.